Heat storage in district heating systems - Turski, Michał (Instal, 2023)
For the further development of district heating systems in terms of the use of renewable energy sources, waste heat and achieving the standard of an energy-efficient heating system, extensive use of heat storage technology is necessary. Heat storage in district heating systems is in line with the principles of sustainable development and the idea of cities of the future. The article presents the justification of heat surplus storage in heating systems by indicating the possible effects of use various storage technologies. The effective solutions included the use of the heat capacity of water, the heat of phase change, as well as central and dispersed heat storage. The achievable relative energy, economic and ecological effects of sensible heat storage may range from 5.1% to 6.38%. The achievable improvement in system efficiency was 21 percentage points when using dispersed heat storage and the latent heat of the phase change. The possible reduction of the source’s heat output was 17.3% with the use of passive heat storage method.